2015
DOI: 10.1007/s10549-015-3559-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of different cut-off levels of Ki-67 in breast cancer: a systematic review and meta-analysis of 64,196 patients

Abstract: A proliferative marker, expressed as the percentage of cells in a cell cycle, has been developed and used as a discriminant of more aggressive malignant phenotypes in early breast cancer (BC). The marker is usually expressed by the immunohistochemical staining of the cell cycle antigen Ki-67. It has not, however, yet been definitely evaluated, due to methodological concerns, which specific Ki-67 cut-off provide the strongest prognostic information in resected BC. We conducted a meta-analysis to explore the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
160
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(180 citation statements)
references
References 64 publications
6
160
1
13
Order By: Relevance
“…Recently, Ki-67 has drawn increasing attention as an attractive prognostic prediction marker and potential therapeutic target in malignant neoplasms. Several studies suggested that Ki-67 is significantly associated with the prognosis of bladder cancer, breast cancer, lung cancer, upper urinary tract urothelial carcinomas, cervical cancer, and lymphoma6933343536. However, the prognostic and clinicopathological values of Ki-67 remain ambiguous in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ki-67 has drawn increasing attention as an attractive prognostic prediction marker and potential therapeutic target in malignant neoplasms. Several studies suggested that Ki-67 is significantly associated with the prognosis of bladder cancer, breast cancer, lung cancer, upper urinary tract urothelial carcinomas, cervical cancer, and lymphoma6933343536. However, the prognostic and clinicopathological values of Ki-67 remain ambiguous in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the Ki‐67 status could be a potential prognostic marker for determining management of patients with ER‐positive breast cancer. Currently, although the National Comprehensive Cancer Network (NCCN) guidelines do not recommend Ki‐67‐based assessment, increasing evidence shows that the Ki‐67 proliferation index is associated with treatment efficacy and survival . A recent meta‐analysis of data from over 6000 patients showed that a high Ki‐67 index is associated with a >50% risk of death and a 64% greater risk of recurrence in patients with early‐stage breast cancer, after adjustment for stage, histological grade, and ER status.…”
mentioning
confidence: 99%
“…A recent meta‐analysis of data from over 6000 patients showed that a high Ki‐67 index is associated with a >50% risk of death and a 64% greater risk of recurrence in patients with early‐stage breast cancer, after adjustment for stage, histological grade, and ER status. Therefore, routine assessment of the Ki‐67 is recommended …”
mentioning
confidence: 99%
“…The Ki‐67 nuclear protein is a key factor of cell cycle progression, which can be demonstrated with high affinity by the antibody clone Mib‐1 . The Ki‐67 labelling index is widely used to estimate proliferative activity, and as such it is an established prognostic factor in different malignant conditions . including lymphoid neoplasias .…”
Section: Discussionmentioning
confidence: 99%